Whole Exome Sequencing reveals NOTCH1 mutations in anaplastic large cell lymphoma and points to Notch both as a key pathway and a potential therapeutic target - Larose, Hugo; Prokoph, Nina; Matthews, Jamie D; Schlederer, Michaela; Högler, Sandra; Alsulami, Ali F; Ducray, Stephen P; Nuglozeh, Edem; Fazaludeen, Feroze M S; Elmouna, Ahmed; Ceccon, Monica; Mologni, Luca; et al. (Haematologica, 2021)
Patients diagnosed with Anaplastic Large Cell Lymphoma (ALCL) are still treated with toxic multi-agent chemotherapy and as many as 25-50% of patients relapse. To understand disease pathology and to uncover novel targets for therapy, Whole-Exome Sequencing (WES) of Anaplastic Lymphoma Kinase (ALK)+ ALCL was performed as well as Gene-Set Enrichment Analysis. This revealed that the T-cell receptor (TCR) and Notch pathways were the most enriched in mutations. In particular, variant T349P of NOTCH1, which confers a growth advantage to cells in which it is expressed, was detected in 12% of ALK+ and ALK- ALCL patient samples. Furthermore, we demonstrate that NPM-ALK promotes NOTCH1 expression through binding of STAT3 upstream of NOTCH1. Moreover, inhibition of NOTCH1 with γ-secretase inhibitors (GSIs) or silencing by shRNA leads to apoptosis; co-treatment in vitro with the ALK inhibitor Crizotinib led to additive/synergistic anti-tumour activity suggesting this may be an appropriate combination therapy for future use in the circumvention of ALK inhibitor resistance. Indeed, Crizotinib-resistant and sensitive ALCL were equally sensitive to GSIs. In conclusion, we show a variant in the extracellular domain of NOTCH1 that provides a growth advantage to cells and confirm the suitability of the Notch pathway as a second-line druggable target in ALK+ ALCL.
Keywords: mutace; Neoplasm Recurrence, Local; Receptor, Notch1; sekvenování exomu; lidé; tyrosinkinasy; receptor Notch1; Exome Sequencing; Protein-Tyrosine Kinases; tyrosinkinasové receptory; Cell Line, Tumor; Receptor Protein-Tyrosine Kinases; Lymphoma, Large-Cell, Anaplastic; Mutation; nádorové buněčné linie; lokální recidiva nádoru; anaplastický velkobuněčný lymfom; Humans